19.2: OLED Lifetime Improvement Based on Optimization of Luminance Compensation Considering Luminance Uniformity. (28th November 2018) - Wang, Hengjie; Fan, Rui; Sun, Chunlai; Zhang, Xiaoning; Hwang, Taijun; Wang, Limin
Abstract : Lifetime is one of the vital factors influencing the OLED displays performance. The existing methods mainly focus on the luminance compensation of OLED pixel to improve lifetime while the OLED luminance uniformity is ignored. The proposed method can optimize luminance compensation and improve luminance uniformity without any sensor. In the proposed method, pixel luminance is compensated while the luminance decays to a setting value. Meanwhile, considering the luminance uniformity, the output grayscale of all pixels of OLED are adjusted based on the actual luminance degradation and input grayscale of each pixel. In addition, luminance non‐uniformity index to evaluate the luminance uniformity is calculated according to the setting weight of each uneven block if the block is considered as uneven blocks. The experimental results indicate that the OLED lifetime can be extended by 28% same as previous method under the luminance compensation optimization and luminance uniformity improvement. Moreover, the luminance non‐uniformity based on human visual characteristics can be improved from 58 to 42.